UPAYA REPRESENTASI IDENTITAS DESA MELALUI PROGAM PEMELIHARAAN GAPURA DESA DAN PEMASANGAN PAPAN EDUKASI SAMPAH - Latifah, Eny; Ummah, Khoirul; Zulistiani, Inne; Yoga Pratama, Putra Andika; Asrori, Achmad; Asy Sya’Bany, Ghulam; Al Hariz, M. Lubab (Jurnal Pengabdian Masyarakat Berkarya, 2025)
The village gate maintenance program and the installation of waste education boards in Cendoro Village were carried out to strengthen village identity and enhance community awareness of environmental cleanliness. This program was implemented through a participatory approach involving village officials, youth organizations, the village-owned enterprise (BUMDES), residents, and local leaders. The methods applied included direct observation, semi-structured interviews, and documentation, followed by data analysis through reduction, presentation, and conclusion drawing with triangulation for data validity. The results revealed that gate maintenance not only improved aesthetic value but also reinforced a collective sense of pride. Meanwhile, the installation of educational boards in strategic locations proved effective as a medium for public learning about waste management. This program has had positive impacts on environmental, social, economic, and cultural aspects, representing Cendoro Village as a community with a strong identity in environmental awareness.